Speaking through the flesh: Affective encounters, gazes and desire in Harlequin romances - Hirdman, Anja (MedieKultur: Journal of media and communication research, 2016)
In the wake of the affective turn, emotion and embodiment have emerged as key terms in cultural studies in order to acknowledge the affective dimension of media texts (Gibbs, 2002; Gregg & Seigworth, 2010). Drawing from the cross-disciplinary field of affect theory, the article examines the writing of desire in Harlequin romances through the delineation of gendered encounters. Against the backdrop of earlier feminist critiques of romance fiction, it argues that Harlequin’s intense focus on corporeal sensations and gazes encompasses a looking relationship that differs significantly from the visual mediation of gender and desire. With its use of an extended literary transvestism, a double narrator perspective, and the appropriation of a female gaze, Harlequin offers readers an affective imaginary space in which the significance of the gendered body is re-made, re-versed, and the male body is stripped of its unique position.